Do PCDD/PCDF standard solutions used in dioxin analysis pose a risk as potentially acutely toxic to lab personnel?. (October 2017) - Malisch, Rainer; Denison, Michael S.; Fiedler, Heidelore; Fürst, Peter; Hoogenboom, Ron L.A.P.; Schaechtele, Alexander; Schrenk, Dieter; van den Berg, Martin
Abstract: Laboratory safety requires protecting personnel from chemical exposures. Working with stock solutions of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/PCDFs) in routine analysis of feed and food with bioanalytical or physicochemical methods raises some concerns. Since PCDD/PCDFs are considered as possibly acutely toxic, the potential risks were evaluated to determine whether supervision of their use is necessary. Based on LD50 -data for oral or dermal intake, hazard classification of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) as a substance (category 1) and in commercially available TCDD standard solutions (category 4) is different. As worst case exposure scenario during routine laboratory work it was assumed that a dose of 100 ng TCDD gets onto the skin and is absorbed. This would result in the total body burden of a 70 kg person with 15 kg fat increasing from 10 (upper range of current background levels) to ∼17 pg of toxic equivalents (TEQs) of PCDD/PCDFs per g lipid, a level commonly observed over past decades. Chloracne, the main acute effect occurring weeks after exposure, is observed at much higher blood concentrations than estimated from accidental laboratory exposure. Immunotoxicity, developmental effects and other toxic effects may occur at lower blood levels, but require longer periods to develop. Since acute toxic symptoms don't occur within an "8 h acute time window", no supervision is necessary when working with standard solutions in routine analysis. Nevertheless, precautionary measures are needed regarding long-term adverse health effects and appropriate workplace conditions must exist to ensure that additional occupational exposure to PCDD/PCDFs by laboratory personnel is negligible. Highlights: Evaluation of dioxin standards as potentially acutely toxic for lab personnel. General aspects of acute toxicity and related hazard categories regarding dioxins. Evaluation of need for a second person at spiking of dioxin standard solutions. Balancing of potential acute risks in a lab "dioxins vs other chemicals". Support of precautionary measures to avoid long-term adverse health effects.